Hydration of Early Age Cement Paste with Nano-CaCO3 and SAP by LF-NMR Spectroscopy: Mechanism and Prediction - Haitao Zhao; Gaoyang Sun; Lu Yu; Kaidi Jiang; Xiaodong Chen; Ruiming Jia; Yi Wan; Shihai Li (Modelling and Simulation in Engineering)
In this paper, by testing the evolution of the physically bound water using the low-field nuclear magnetic resonance (LF-NMR) technology, the hydration process of cement paste with nano-CaCO3 (NC) and superabsorbent polymer (SAP) at early age is investigated. Results indicate that the hydration process can be divided into four periods according to the zero points of the second-order differential hydration curve: initial period, acceleration period, deceleration period, and steady period. Firstly, with the increase in the water to cement ratio, the starting time of the hydration period is delayed, and the duration becomes longer. Secondly, the addition of NC leads to the speedy arrival of each period and shortens the duration of each period in the hydration process, and the optimal NC content is 1.5%. Thirdly, with the increase in SAP content, the starting time of the hydration period is delayed and the duration becomes longer. Finally, based on the experimental results and the existing hydration model, the modified hydration model considering the content of NC and SAP is proposed.